(3GdJHjGf GdLGeY Hjf GdMce hGdHjGfs - (3eMeO Hf MSf hGOj Hf Ydj Hf NRGe GdUjGOj , CHh GdgOj,J (B1328 (3g` s
(3ChdgG (B:s
(3GeG HYO (B: (3ajbhd GdYHO Ef GdTYQ fJjLI GdYbd bGd (B: (3GHh GdYHGS eMi GdOjf GdSjO CMeO GdQaGYi GdcHjQ GdcdGe Sja Gddg GdPi jLeY Hg hjaQb hdeG cJGf GdefXhe CbQH ddCPgGf MaXg s
(3BNQgG (B:s
(3GLJPHJge Edi Gddg GdCThJb hGdGHJgGL HeOM YXje cQje , Pi bOe QGSN heLO Ueje , hGdETGQI Edi GdbOM HdFje Rfje hGddg GdeSDd Cf jDjO GdOjf hGdeSdejf , hCf jYdi cdeI GdMb hGdeHjf s
(3OjhGf TYQs
(3gfGc Tc ai Cf eDda GdeNWhW gh fGSNgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B226s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B137 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs